Religion og deltakelse: Moskeen som kjønnet arena - Predelli, Line Nyhagen (Kvinder, Køn & Forskning, 2005)
The article discusses the participation of immigrant Muslim women in mosques in Oslo. Muslim women have to relate to a religiously given patriarchal structure, but are also actors that can make choices and take advantage of possibilities that challenge patriarchal gender regimes. At times, complex and contradictory processes increase the participation of women, while at other times they constrain women’s activities through various forms of discipline and control. The study shows that immigrant women are decisive for the building of religious institutions among Muslim migrants in diaspora, and that women tend to achieve greater space and be included in more varied forms of participation in the mosque after migration. Despite signs of increased participation by women, the mosque may still be described as a patriarchal gender regime where such participation to a large extent depends on the goodwill of men.